Bibliometric analysis of research trends in islamic family law and counseling: a global perspective (1988–2024) - Simbolon, Parlindungan; K, Hendri; Zatrahadi, M. Fahli (COUNS-EDU: The International Journal of Counseling and Education, 2024)
This study aims to identify and analyze research trends in Islamic family law and counseling from 1988 to 2024 using a bibliometric approach. Islamic family law is an important branch of Islamic law that has a direct influence on the social, spiritual, and psychological life of Muslims. In the face of global social changes, such as secularization, family value shifts, and issues of gender justice and child protection, a more contextual understanding of the application of Islamic family law is needed. In this context, a counseling approach emerged as an important alternative to accommodating the emotional, psychosocial, and spiritual needs of Muslim families. This study analyzed 229 documents taken from the Scopus database, then filtered them through a systematic approach until 17 relevant major publications were obtained. Analysis was conducted with the help of VOSviewer and RStudio software to map keywords, thematic relationships, and collaboration networks between authors and journals. Research results show that the dominant issues that arise include child marriage, polygamy, inheritance, women's rights, family mediation, and interfaith marriage. Thematic cluster visualization highlights five main focuses in the discussion of Islamic family law that are interconnected with contemporary social and cultural issues. This study asserts that the integration between Islamic legal norms and counseling approaches can strengthen the resilience of Muslim families, as well as provide solutions that are not only legal-formal, but also empathic, adaptive, and sustainable. This finding is expected to be the basis for the development of Islamic law that is more responsive to the dynamics of modern society.